SISTEM PENGELOLAAN TERMINAL MANGKANG KOTA SEMARANG - Sushernawan, Prasetya; ., Sulistyowati; ., Fitriyah (Journal of Politic and Government Studies, 2014)
This study, entitled "SYSTEM MANAGEMENT TERMINAL CITY MangkangSemarang". Terminal Mangkang a master terminal type A that is in the province of CentralJava is managed by Dishubkominfo. Terminal is a facility for public service units, as publicfacilities, the terminal should be able to provide services to the community as well as possible.So that they can be expected to contribute the maximum to PAD (the original income) withoutcompromising service to the community.Formulation of the problem in this research study on how patterns lead managementsystem available on the Terminal Mangkang. The research was conducted using qualitativedescriptive method research location in Terminal Mangkang Semarang. Informant selectiontechniques were performed using descriptive analytical techniques.In the terminal management Mangkang Semarang, Dishubkominfo still manyshortcomings both in terms of service and comfort in the terminal Mangkang so impresseddeserted, there needs to be an increase in services.All parties involved in the management process Mangkang Semarang terminal shouldbe together so that the optimization process can be better Mangkang Terminal and inaccordance with the potential of Semarang society.Keywords: management of systems, Terminal